Reviews of Books (International review of mission, 1926)
Book reviewed in this article: A STUDY OF REACTIONS: Christian Missions and Oriental Civilizations. By Maurice T. Price SOME BIOGRAPHIES OF PIONEERS: Robert Moffat: One of God's Gardeners. By Edwin W. Smith SOME BIOGRAPHIES OF PIONEERS: Robert Hellier Napier in Nyasaland: Being his Letters to his Home Circle. Edited by Alexander Hetherwick SOME BIOGRAPHIES OF PIONEERS: The Autobiography of Theophilus Waldmeier, 1832–1915. Edited by Stephen Hobhouse SOME BIOGRAPHIES OF PIONEERS: Samuel Reynolds House of Siam: Pioneer Medical Missionary, 1847–1876. By G. H. Feltus SOME BIOGRAPHIES OF PIONEERS: Gilmour of the Mongols. By W. P. Nairne SOME BIOGRAPHIES OF PIONEERS: The Son of a Savage: The Story of Daniel Bula. By R. C. Nicholson SOME BIOGRAPHIES OF PIONEERS: Felix Westerwoudt: Missioner in Borneo. By E. v. R. W. THE AO NAGAS: The Ao Naga Tribe of Assam. By William Carlson Smith SEEKERS AFTER GOD: The Quest for God in China. By F. W. S. O'Neill THEOLOGICAL EDUCATION IN CHINA: Education of Christian Ministers in China. By Samuel H. Leger JAPAN AND CHRISTIANITY: The Task in Japan: A Study in Modern Missionary Imperatives. By A. K. Reischauer AFRICAN CHRISTIANS AND ISLAM: Islam and Africa: An Introduction to the Study of Islam for African Christians. By Godfrey Dale SOME ROMAN CATHOLIC BOOKS ON MISSIONS: Along the Mission Trail. By Bruno Hagspiel SOME ROMAN CATHOLIC BOOKS ON MISSIONS: Africa, 1925. By William G. McMenemy.—An Outline History of Christian Missions. By Paul A. Gieringer A CHURCH AND ITS MISSIONARY TASK: The World Call to the Church: The Call from Africa (2s. 6d.); The Call from India (2s. 6d.); The Call from the Far East (3s.); The Call from the Moslem World (2s. 6d.)